Identification of methylated GnTI‐dependent N‐glycans in Botryococcus brauni. Issue 4 (24th July 2017) - Schulze, Stefan; Urzica, Eugen; Reijnders, Maarten J. M. F.; van de Geest, Henri; Warris, Sven; Bakker, Linda V.; Fufezan, Christian; Martins dos Santos, Vitor A. P.; Schaap, Peter J.; Peters, Sander A.; Hippler, Michael
Summary: In contrast to mammals and vascular plants, microalgae show a high diversity in the N ‐glycan structures of complex N ‐glycoproteins. Although homologues for β1, 2‐ N ‐acetylglucosaminyltransferase I (GnTI), a key enzyme in the formation of complex N ‐glycans, have been identified in several algal species, GnTI‐dependent N ‐glycans have not been detected so far. We have performed an N ‐glycoproteomic analysis of the hydrocarbon oils accumulating green microalgae Botryococcus braunii . Thereby, the analysis of intact N ‐glycopeptides allowed the determination of N ‐glycan compositions. Furthermore, insights into the role of N ‐glycosylation in B. braunii were gained from functional annotation of the identified N ‐glycoproteins. In total, 517 unique N ‐glycosylated peptides have been identified, including intact N ‐glycopeptides that harbored N ‐acetylhexosamine (HexNAc) at the nonreducing end. Surprisingly, these GnTI‐dependent N ‐glycans were also found to be modified with (di)methylated hexose. The identification of GnTI‐dependent N ‐glycans in combination with N ‐glycan methylation in B .  braunii revealed an uncommon type of N ‐glycan processing in this microalgae.